Pulmonary and systemic immune alterations in rats exposed to airborne lunar dust - Crucian, Brian E.; Quiriarte, Heather; Lam, Chiu-wing; Nelman, Mayra; Colorado, Audrie A.; Diak, Douglass M.; James, John T. (Frontiers in Immunology, 2025)
BackgroundDue to cosmic radiation bombardment and over 4 billion meteorite and micrometeoroid impacts on the airless Moon, the lunar surface is covered by a layer of fine, reactive dust. Very little is known regarding the toxicity of lunar dust on human physiology. This study assessed airborne lunar dust exposure in rats on localized pulmonary and systemic immune parameters.MethodsRats were exposed to 0 (air only), 20.8 (low), and 60.6 (high) mg/m3 of respirable-size lunar dust for 4 weeks (6 h/day, 5 days/week). Rats were then euthanized either 1 day, 7 days, 4 weeks, or 13 weeks after the last exposure. Peripheral blood and lung lavage fluid samples were collected for analysis. Assays included leukocyte distribution by multicolor flow cytometry and electron/fluorescent microscopy to visualize cell–particulate interactions and lavage/plasma cytokine concentration. Mitogen-stimulated cytokine production profiles, as a measure of cellular function, were performed on whole blood samples only.ResultsUntreated lavage fluid was comprised primarily of pulmonary macrophages. High-dose lunar dust inhalation (60.6 mg/m3) resulted in an influx of both neutrophils and lymphocytes. Although the percentage of lymphocytes increased, the T-cell CD4:CD8 ratio was unchanged. Cytokine analysis of the lavage fluid showed increased levels of IL-1β and TNFα. These alterations generally persisted through the 13-week sampling. Blood analysis showed few systemic immune alterations from the lunar dust inhalation. By week 4, the peripheral granulocyte percentage was elevated in the treated rats. Plasma cytokine levels were unchanged in all treated rats compared to controls; however, altered mitogen-stimulated cytokine production profiles were observed consisting of increased IL-1β and IL-6 and decreased IL-2. There were minimal adverse immune effects, in both lung or peripheral blood, following low-dose exposure to 20.8 mg/m3 lunar dust.ConclusionExposures to high concentrations of lunar dust resulted in persistent lung inflammation and some systemic immune dysregulation that did not subside even 13 weeks after the dust exposure. This information is beneficial in deriving an exposure limit to airborne lunar dust and for spacecraft engineers considering dust mitigation systems in lunar landers or habitats.